Cardiac Microtissues: Maladaptive Contractility of 3D Human Cardiac Microtissues to Mechanical Nonuniformity (Adv. Healthcare Mater. 8/2020). Issue 8 (22nd April 2020) - Wang, Chenyan; Koo, Sangmo; Park, Minok; Vangelatos, Zacharias; Hoang, Plansky; Conklin, Bruce R.; Grigoropoulos, Costas P.; Healy, Kevin E.; Ma, Zhen
Abstract : In article number 1901373 by Kevin E. Healy, Zhen Ma, and co‐workers, a "pathologically‐inspired" 3D cardiac microtissue model is established based on human induced pluripotent stem cells and laser‐based 3D printing technology. This engineered in vitro model system can facilitate better understanding of the correlation between cardiac contractile dysfunctions and nonuniform tissue mechanical environments.